Design of a Web-Based Interactive Digital Book (E-Book) Application (Case Study: Politeknik Bisnis Digital Indonesia) - Pratama, Riski Adi; Panpora, Tutur; Wibowo, Trie Hanoto; Arisantoso , Arisantoso (Jurnal Indonesia Sosial Sains, 2025)
This research aims to design and develop a web-based e-book application at the Politeknik Bisnis Digital Indonesia. With the rapid development of digital technology, educational institutions need to provide efficient and flexible solutions for accessing learning materials. This e-book system is designed to make it easier for students and lecturers to access digital books anytime and anywhere, without relying on physical availability in the library. The method used in this study is software engineering with the Waterfall approach, including needs analysis, system design, implementation, testing, and maintenance. The results of the study show that this e-book system not only reduces the cost of purchasing and printing physical books but also improves library operational efficiency and learning quality. With features such as user management, e-book management, and digital book readers, the system is expected to support online and hybrid learning on campus. This research makes a significant contribution to improving digital literacy among students and lecturers and preparing campuses to face the era of digital education.